Cardamonin inhibited cell viability and tumorigenesis partially through blockade of testes-specific protease 50-mediated nuclear factor-kappaB signaling pathway activation. (April 2016) - Mi, Xu-Guang; Song, Zhen-Bo; Sun, Lu-Guo; Bao, Yong-Li; Yu, Chun-Lei; Wu, Yin; Li, Yu-Xin
Abstract: Previous studies have shown that testes-specific protease 50 (TSP50), a pro-oncogene overexpressed in many types of tumors, could promote cell proliferation, invasion, tumorigenesis, and tumor metastasis, suggesting that it is a potential cancer therapeutic target in drug discovery. Here, a luciferase assay system driven by the TSP50 gene promoter was used to screen the inhibitor of expression of TSP50. The study found that cardamonin, a flavone compound, could efficiently inhibit the expression of TSP50 in both mRNA and protein levels. Further results revealed that cardamonin also efficiently inhibited the viability of TSP50 high-expressing cancer cells by inducing G2/M-phase arrest and mitochondrial-dependent apoptosis. Surprisingly, knocking down the expression of TSP50 gene had the same effects as treatment with cardamonin. Moreover, it has been found that cardamonin had an inhibitory potency on TSP50 high-expressing tumor growth in vivo. In contrast, overexpression of TSP50 greatly decreased the cell sensitivity to the inhibitory effect of cardamonin and reversed the decreased tumor-inhibitory effect of cardamonin. Additionally, both TSP50 interference and treatment with cardamonin could suppress p65 nuclear translocation, and overexpression of TSP50 reversed the suppressive effect of cardamonin on p65 nuclear translocation. Taken together, these results suggest that cardamonin inhibited cell viability and tumorigenesis at least partially via blocking the activation of TSP50-mediated nuclear factor-kappaB signaling pathway, and cardamonin may be a promising anticancer drug candidate in the development of a novel agent for TSP50 high-expressing cancer cells.